Problemas funcionais na alimentação de idosos institucionalizados - Baldissera, Patrícia Ribak (2021)
Population aging has been increasing worldwide, which reflects the growing number of people living in long-term care. The eating problems that can be faced by the elderly directly influence their food consumption and consequently their nutritional status and health. This study aims to verify the prevalence of eating difficulties and their associated factors in elderly residents, describing the sociodemographic characteristics of the sample, and identifying the prevalent diseases in long-term care facilities and their possible association with eating problems. Therefore, a cross-sectional study was conducted with the elderly residents of nursing homes and assisted living communities in the cities of Passo Fundo (RS), Bento Gonçalves, and Carazinho (RS) in 2017. This study is a part of the research “Aging patterns and longevity: biological, educational and psychosocial aspects”. A standardized questionnaire with the following variables was used: sociodemographic, Mini Nutritional Assessment, and Mini-Mental State Examination. The outcome, eating problems, was assessed using five questions and categorized into the presence or absence of problems, if any of the questions were positive. For qualitative variables, univariate frequency distributions, bivariate and multivariate contingency tables were used. Quantitative variables were described using measures of central tendency and variability. To assess the association between categorical variables, Pearson's chi-square test, Fisher's exact test, and prevalence ratio with a 95% confidence interval was applied. The significance level was 5%. Multivariate analysis was performed using Poisson Regression. A total of 469 elderly residents were evaluated, most of them female and approximately one third had functional feeding problems. The presence of functional problems in feeding was associated with the nutritional status, the presence of stroke and dementia. The results show the importance of tracking the factors associated with food consumption and eating habits among the elderly residents, to develop prevention strategies and support intervention protocols, improving health, nutritional status, and the quality of life of the elderly residents. This dissertation is composed of an introduction, literature review, the scientific article I, conclusion and references.